Snakes of Central and Western Africa - Chippaux, Jean-Philippe (Johns Hopkins University Press, 2019)
"This book is the first and only comprehensive guide to the snakes of Central and Western Africa. In North America, field guides are taken for granted, but for much of the world these guides don't exist. In many high biodiversity areas of the third world, even the specialist is stumped by many specimens. Jean-Philippe Chippaux and Kate Jackson have a combined half-century of experience studying these snakes in the field. Covering identification, evolution, behavior, and occurrence, Snakes of Central and Western Africa also features maps, photos, and drawings for each species to aid in identification. Each year 20,000 people die from snake bites in Africa, and this problem can only worsen with the increasing human presence in these habitats. While poverty, transportation, and the availability of medical care are all problems that must be addressed, a sound knowledge of the species is the necessary first step. An essential read, which, ultimately, can save lives"--